ADAMTS13 mutations and polymorphisms in congenital thrombotic thrombocytopenic purpura - Lotta, Luca A; Garagiola, Isabella; Palla, Roberta; Cairo, Andrea; Peyvandi, Flora (Human mutation, 2010)
Congenital thrombotic thrombocytopenic purpura (TTP) (also known as Upshaw-Schulman syndrome, USS) is a rare, life-threatening disease characterized by thrombocytopenia and microangiopathic hemolytic anemia, associated with the deficiency of the von Willebrand factor-cleaving protease (ADAMTS13) due to mutations in the corresponding gene. The spectrum of clinical phenotype in congenital TTP is wide, encompassing neonatal-onset disease and adult-onset disease, forms with a single disease episode and chronic-relapsing forms. We review ADAMTS13 gene variants associated with inherited ADAMTS13 deficiency and congenital TTP. To date, 76 mutations of ADAMTS13 are reported in the literature. Missense mutations, which constitute nearly 60% of ADAMTS13 mutations, preferentially localize in the 5′-half of the gene encoding the N-terminal half of the protein, where the domains that are indispensable for ADAMTS13 catalytic function are situated. In vitro expression studies in cell cultures have shown that defects in protein secretion and catalytic activity are the main mechanisms responsible for the deficiency of ADAMTS13 in congenital TTP patients. Even if data from the literature suggest the existence of genotype-phenotype correlations, a clear relationship between the type and the effect of ADAMTS13 genetic defects with disease manifestations remains to be established. Hum Mutat 30:1-9, 2009.